Perancangan Enterprise Architecture menggunakan TOGAF ADM pada PT. Mandiri Leader Cargo - Angelina Mega Leltakaeb; Yulhendri (Prosiding SISFOTEK, 2025)
The business world has undergone significant changes as a result of digital transformation, including the logistics sector, which requires information system integration and efficiency. Businesses can now optimize their operational processes and become more competitive thanks to advances in information technology. PT. Mandiri Leader Cargo (MLC), a freight forwarding company operating via air and land routes, still faces difficulties in running its operations due to the lack of an integrated information system. Processes such as fleet scheduling, monitoring delivery status, and reporting are still carried out manually through verbal communication, WhatsApp, and Excel. This leads to inefficiency and errors. The purpose of this research is to create an Enterprise Architecture (EA) using the TOGAF ADM approach, starting from the preliminary phase to Opportunities and Solutions. The design results in a blueprint for an integrated business architecture, applications, data, and technology, with a focus on the development of three main modules: Pick-Up, Outgoing Tracking, and Outgoing Report. It is expected that this design will improve operational processes, enhance coordination between divisions (Customer Service, Fleet, Warehouse, Gateway, and Finance), and enhance the quality of service and competitiveness of PT. MLC in the domestic logistics industry